Investigation of rumen metagenome in Italian Simmental and Italian Holstein cows using a whole-genome shotgun sequencing technique. Issue 4 (2nd October 2018) - Sandri, Misa; Licastro, Danilo; Dal Monego, Simeone; Sgorlon, Sandy; Stefanon, Bruno
Abstract: The study aimed at investigating the rumen microbiome composition and functional activity in mid lactating cows of Italian Holstein (IH) and Italian Simmental (IS) breeds. Eight IH and eight IS pluriparous cows with days in milking (DIM) ranging from 90 to 180 were selected and rumen contents were sampled with oesophageal tube. Rumen metagenome was analysed using a whole shotgun sequencing. Data were analysed for taxonomic classification and microbial genes. The relative abundance of Archaea, the Archaea to Bacteria ratio and the Archaea to Eukarya ratio were higher ( p  < .05) in IS than IH cows. The comparison between IH and IS underlined differences for the abundances of Bacteria, being Bactroidaceae, Bacteroides, Prevotellaceae and Prevotella lower ( p  < .05) in IS than in IH cows. The IS cows showed higher abundances of Euryarchaeota ( p  < .05), Methanosphera ( p  < .01) and Methanothermobacter ( p  < .05) than IH cows. The annotation of sequences to KEGG revealed that 170 genes were differentially abundant between IS and IH cows and among these, 20% were involved in protein biosynthesis, 8.8% in one-carbon metabolism, as methyl coenzyme M reductase associated protein and of six isoforms of methyl coenzyme M reductase. The present results suggest a genetic link between breed and microbiome, although this interaction can be influenced by several biological factors. Considering that there are still a low number of whole genome shotgun sequencing analysis of rumen communities, these data can provide further information to scientific community.